TEACHER’S ACTTITUDES TO CLASSROOM BEHAVIORAL INTERVENTION - Herrera Barranco, Joaquín; Pavón Delgado, Inmaculada; Moreno García, Inmaculada (Anales de Psicología / Annals of Psychology)
A questionnaire is described to evaluate the teachers’ attitude towards the conductual interventions in the school. 120 teachers from E.G.B. and 60 students from the last course of the Teaching College have contributed of the following points: the Specialization in Special Teaching and the Professional Teaching Experience. The results showed the usefulness of the questionnaire in relation to our objectives. There are some important differences between teachers trained in Special Teaching. The differences we have found according to the professional teaching experience are not relevant.